Relative length as a classification parameter of the crystallization mode of amorphous films - Bagmut, A.G. (Вопросы атомной науки и техники, 2022)
The possibility of using of the relative length δ₀ as a parameter, determining the polymorphous crystallization mode of amorphous films, was considered. Following polymorphous crystallization modes have been identified based on the structural and morphological characteristics. Layer polymorphous crystallization mode, describes the nucleation and growth of a single-crystal layer in the field of the electron-beam impact, for which δ₀ is about several thousand (3000…5000). Island polymorphous crystallization mode, describes the nucleation and growth of a polycrystalline layer, for which δ₀ is about several hundred (100…1100). Dendrite polymorphous crystallization mode, describes the nucleation and growth of dendrite, for which δ₀ is about several thousand (∼ 4000).